Moving inquiry-based learning forward: A meta-synthesis on inquiry-based classroom practices for pedagogical innovation and school improvement in the humanities and arts - Costes-Onishi, Pamela; Baildon, Mark; Aghazadeh, Sima (Asia Pacific journal of education, 2020)
The challenges of the 21st century place inquiry as a necessary pedagogical orientation to educate young people for the future. In Singapore, inquiry-based learning is a core feature in social studies and the humanities subjects (geography and history) and has been extended recently to curriculum in the arts. Its centrality in the education system has been well acknowledged by Singapore's Ministry of Education. However, an examination of research focusing on inquiry-based learning in Singapore has revealed that inquiry instruction remains teacher-centred and teachers are unsure about how to use inquiry as a core pedagogical approach. This article presents a meta-synthesis from the international literature, as well as studies in Singapore, to generate a theory on impactful forms of inquiry-based classroom practices for pedagogical innovation and school improvement. The article concludes that students learn best, in terms of conceptual understanding and higher-order thinking, when they are experientially and collaboratively engaged in the search for meanings, solving problems, questioning, sharing and communicating their understanding. Finally, the article argues for the importance of building an inquiry culture, mindsets and social practice in order to address the broader challenges to inquiry-based instruction from a systems or ecological view.